Hypotension: An Overview of Updated Data for Healthcare Providers - Alghubaywi, Bader Khalid Ghayib; Albaqami , Hatim Abdullah; Alharbi, Fawaz Awad; Altherwi, Turki Abdulbari; Ai-Otaibi, Khudhayr Badar Khudhayr; Alqahtani , Shodaiyed Masoud; Alamer , Fatimah Ahmed; Alhamamah , Omar Sulaiman Hamad; Alharbi, Raed Mohammed Abdulaziz; Alotaibi , Sara Metaib; Aldawsari, Mohammed Faleh; Alrasheedi, Hani Salem Salman; et al. (Journal of Ecohumanism, 2024)
Background: Hypotension, defined as a reduction in systemic blood pressure below normative thresholds (typically <90/60 mmHg), is often asymptomatic but can become clinically significant when it impairs perfusion to vital organs. It is classified into absolute, relative, orthostatic, and profound types, with acute hypotensive shock representing a life-threatening condition. Blood pressure regulation depends on cardiac output and total peripheral vascular resistance, with disruptions in these mechanisms leading to hypotension. Aim: This article aims to provide an updated overview of hypotension, including its etiology, pathophysiology, clinical presentation, diagnostic evaluation, and management strategies, to enhance healthcare providers’ understanding and improve patient outcomes. Methods: The review synthesizes current data on hypotension, focusing on its classification, hemodynamic principles, and underlying causes. Diagnostic approaches, including laboratory tests, imaging studies, and hemodynamic assessments, are discussed. Management strategies, such as fluid resuscitation, vasopressor use, and treatment of underlying conditions, are outlined. Results: Hypotension arises from various etiologies, including reduced cardiac output, decreased peripheral vascular resistance, or a combination of both. Diagnostic tools such as echocardiograms, CT angiograms, and pulse pressure variation aid in identifying the cause. Treatment focuses on addressing the underlying etiology, with vasopressors and fluid resuscitation being key interventions in acute settings. Prognosis varies, with benign hypotension having an excellent outcome, while symptomatic or shock-related hypotension carries higher morbidity and mortality. Conclusion: Effective management of hypotension requires a thorough understanding of its pathophysiology, accurate diagnosis, and tailored treatment. An interprofessional approach involving physicians, nurses, pharmacists, and allied health professionals is essential for optimizing outcomes, particularly in acute or life-threatening scenarios